Embryonic Stem Cell Transplantation - Karpenko, A. V.; Bugayev, V. N.; Smikodub, A. I.; Yurchenko, Т. N. (Problems of Cryobiology and Cryomedicine, 2002)
The results of long-term clinical investigations of treating patients with diabetes, oncological and hematological diseases using the transplantations of embryonic cellular suspensions are presented: a persistent decrease in the essential daily insulin dose in insulindependent diabetes mellitus, increase in the periods and depth of remission, reduction of compli-cations’ manifestations (anemia, dystrophy,etc); rapid recovery of granulocytes number (3 to 7 days) and blood count in myelotoxic agranulocytoses in oncology and hematology patients, increase in tolerance to chemotherapy, reduction of relapses and metastasising, quality life improvement, a considerable increase in psychoemotional status, decrease in depression component. The sources of stem cells (SCs) are discussed, the unacceptability of material from viable embryos after artificial fertilisation is stated. Legislative and methodological base for the development and coordination of research in the field of embryonic stem cells (ESCs) transplantation is provided.